Are rootzone soil moisture dynamics and thresholds associated with surface layer? - Sandipan Paul; Andrew F Feldman; L Karthikeyan (Environmental Research Letters)
The identification of evapotranspiration regimes, primarily the water-limited and energy-limited regimes, separated by the critical soil moisture (CSM) threshold, is fundamental to analyzing land–atmosphere interactions. To better understand the soil moisture (SM) dynamics happening synchronously in the soil column, we aim to estimate the rootzone (0–28 cm and 0–100 cm) CSM thresholds and associated regimes at a global scale, which was not previously attempted. We propose the use of the covariability of soil diurnal temperature amplitude (derived from the GLDAS) and SM (ERA5) to estimate the CSM, which overcomes the data uncertainty and multivariate dependencies of traditional methods. We find that transitional climatic regions, encompassing the western USA, Brazilian savanna, Sahelian grassland, South African savanna, peninsular India, and Mediterranean region, are global hotspots of frequent rootzone regime shifting with significant seasonality—the wet regime prevails in the fall season, while the dry regime takes over at other times of the year. The CSM values of 0–28 cm and 0–100 cm layers are mostly in the 0.2–0.35 and 0.25–0.4 m ^3 m ^−3 range, respectively. We find that landscape aridity and bioclimatic characteristics primarily determine the spatial distribution of CSM and associated regimes. Furthermore, we investigate the hydrological link between the surface and rootzone layers. We note that the rootzone and surface CSM and regimes are strongly correlated, although the 0–28 cm layer indicates a relatively stronger connection compared to the 0–100 cm layer. The shallower (deeper) rootzone layer shows regimes similar to those on the surface for more than 80% (65%–80%) of the time. We observe that the strength of association between surface and rootzone regimes increases from arid (herbaceous vegetated regions) to humid (woody) regions and during wet to dry seasons. Overall, a strong association in regime dynamics between surface and subsurface layers suggests the potential applicability of remotely sensed surface SM as a surrogate to study rootzone regime responsiveness to soil–plant–atmosphere interactions.